2020
DOI: 10.5194/gmd-13-4287-2020
|View full text |Cite
|
Sign up to set email alerts
|

Modelling mineral dust emissions and atmospheric dispersion with MADE3 in EMAC v2.54

Abstract: Abstract. It was hypothesized that using mineral dust emission climatologies in global chemistry climate models (GCCMs), i.e. prescribed monthly-mean dust emissions representative of a specific year, may lead to misrepresentations of strong dust burst events. This could result in a negative bias of model dust concentrations compared to observations for these episodes. Here, we apply the aerosol microphysics submodel MADE3 (Modal Aerosol Dynamics model for Europe, adapted for global applications, third generati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 74 publications
(146 reference statements)
0
43
0
Order By: Relevance
“…Hence, the contribution of cirrus clouds formed in-situ by heterogeneous and/or homogeneous ice nucleation and cirrus clouds resulting from transport of ice from the mixed phase (e.g., via detrainment from convective clouds) should be further explored. The representation of background aerosol like soot and mineral dust was already demonstrated to be quite good by Kaiser et al (2019), Righi et al (2020) and Beer et al (2020). Nevertheless improvements are still possible, especially with the support of in situ measurements.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, the contribution of cirrus clouds formed in-situ by heterogeneous and/or homogeneous ice nucleation and cirrus clouds resulting from transport of ice from the mixed phase (e.g., via detrainment from convective clouds) should be further explored. The representation of background aerosol like soot and mineral dust was already demonstrated to be quite good by Kaiser et al (2019), Righi et al (2020) and Beer et al (2020). Nevertheless improvements are still possible, especially with the support of in situ measurements.…”
Section: Discussionmentioning
confidence: 98%
“…As a basis for aerosol classification in the present study, we analysed one of the global model simulations of Beer et al (2020) performed with the global aerosol model EMAC-MADE3. MADE3 simulates nine different aerosol species (sulphate, ammonium, nitrate, the sea salt species sodium and chloride, BC, POM, mineral dust and aerosol water).…”
Section: Model Description and Configurationmentioning
confidence: 99%
“…Kaiser et al (2019) further demonstrated the good agreement of MADE3 simulated BC, POM, gaseous species and particle number concentrations with various observations. Beer et al (2020) extended the model setup of Kaiser et al (2019) by including an online parametrization for wind-driven dust emissions (Tegen et al, 2002). The authors performed five model experiments for the time period 2000-2013 applying different horizontal and vertical model resolutions.…”
Section: Model Description and Configurationmentioning
confidence: 99%
See 2 more Smart Citations